Dua Space Dance Theatre of Malaysia: Exploring Wheelchair Dance - Leng Poh Gee (Wacana Seni Journal of Arts Discourse, 2024)
Dua Space Dance Theatre, founded by Anthony Meh and Aman Yap in 1998, is a full-time contemporary dance company emphasising technical virtuosity and narrative choreography and often selecting themes centred on the local Chinese community. The dance company is highly associated with highlighting intercultural collaboration and embracing diversity. In 2006, with the nebular concept of Shang Jian Yi Jia (one family regardless of whether disabled or normal), Anthony and Aman were invited to establish a wheelchair dance troupe, Shuang Fu Performing Arts Troupe. This article explores the interaction between Dua Space Dance Theatre and Shuang Fu Performing Arts Troupe in terms of dance training, performance, artistic development, and its contribution to the collaboration of international disabled dance practitioners and producers. Their collaboration promotes innovation in dance-making, advocates accessibility to dance appreciation, and challenges disability stereotypes. Through interviews and archival research, this article re-visits the direction concept of Shang Jian Yi Jia, which has been practised since 2006. Through the lens of the four dimensions of social inclusion within the context of performing arts, this article identifies the Dua Space Dance Theatre’s expertise in making and performing wheelchair dance and suggests its potential for development that creates space for the visibility of disabled dancers.